The levels of natural Nosema spp. infection in Apis mellifera iberiensis brood stages - Urbieta-Magro, Almudena; Higes, Mariano; Meana, Aránzazu; Gómez-Moracho, Tamara; Rodríguez-García, Cristina; Barrios, Laura; Martín-Hernández, Raquel (International journal for parasitology, 2019)
[Display omitted] •Nosema ceranae and Nosema apis naturally infect a honey bee brood, both larvae and pupae.•Brood infection is not related to the presence of spores inside the brood cell.•The level of infection in a brood is much lower than in adult bees. Nosema ceranae is the most prevalent endoparasite of Apis mellifera iberiensis and it is a major health problem for bees worldwide. The infective capacity of N. ceranae has been demonstrated experimentally in honey bee brood, however no data are available about its prevalence in brood under natural conditions. Thus, brood combs from 10 different hives were analyzed over two consecutive years, taking samples before and after winter. A total of 1433 larvae/pupae were analyzed individually and N. ceranae (3.53%) was the microsporidian most frequently detected, as opposed to Nosema apis (0.42%) which was more frequently detected in conjunction with N. ceranae (0.71%). The active multiplication of both microsporidians was confirmed by the expression (real-time-PCR) of the N. ceranae polar tube protein 3 gene and/or the N. apis RNA polymerase II gene in 24% of the brood samples positive for Nosema spp. Both genes are related to microsporidian multiplication. As such, N. ceranae multiplication was confirmed in 1.06% of the samples, while N. apis multiplication was only observed in co-infections with N. ceranae (0.07%). Brood cells were analyzed for the presence of Nosema spp., as those are the immediate environment where the brood stages develop. The brood samples infected by Nosema spp. were in brood cells in which that microsporidians were not detected, while brood cells positive for N. ceranae hosted brood stages that were not apparently infected, indicating that this is unlikely to be the main pathway of infection. Finally, the colonies with brood infected by N. ceranae showed higher levels (numbers) of infected adult bees, although the differences were not significant before (P = 0.260), during (P = 0.055) or after (P = 0.056) brood sampling. These results show that N. ceranae is a bee parasite ubiquitous to all members of the colony, irrespective of the age of the bee. It is also of veterinary interest and should be considered when studying the epidemiology of the disease.